Sanksi Terhadap Pelaku Tindakan Penyalahgunaan Nomor Induk Kependudukan Sebagai Pengurus Partai Politik - I Gusti Ngurah Putra Pratama; I Gusti Bagus Suryawan; Indah Permatasari (Fakultas Hukum Universitas Warmadewa, 2025)
This identity card contains personal identity information such as facial identity, place, and date of birth of the individual concerned. This identity card will serve various purposes besides being population data residing in a certain area. This policy is referred to as the use of an electronic identity card, which will henceforth be called E-KTP. The implementation of E-KTP aims to ensure that every citizen who possesses this electronic identity card has only one official record to be applied throughout all administrative sectors in Indonesia. Political parties are new organizations that emerged in the 1830s as part of modern democracy, representative democracy. Political parties in political institutions play a role for the state, as they act as a unifying force in conveying the aspirations of the people and moving towards freedom. In this way, someone who is not interested in joining a political party could become a candidate member. The problems formulated in this research include (1) How is the Legal Protection for Victims of Abuse of Population Identification Numbers as Political Party Administrators? and (2) What are the Sanctions against perpetrators of Abuse of Population Identification Numbers as Political Party Administrators? This writing uses the method of normative legal research. The result of the analysis is Legal Protection for Victims of Abuse of Population Identification Numbers as Political Party Administrators. Additionally, there are Sanctions against perpetrators of Abuse of Population Identification Numbers as Political Party Administrators.